Direct Organocatalytic Construction of Bicyclo[3.2.1]octanes by Domino Michael/Aldol Reaction with β,γ-Unsaturated 1,2-Keto Amides - Lefranc, Alice; Guénée, Laure; Goncalves-Contal, Sylvie; Alexakis, Alexandre (Synlett, 2014)
A direct construction of bicyclo[3.2.1]octanes by an organocatalytic domino Michael/Aldol reaction of cyclic 1,3-keto esters with β,γ-unsaturated 1,2-keto amides is reported. Formation of a precipitate corresponding to the racemic co-crystals of the bicyclic compound was observed in toluene, whereas a homogeneous solution was obtained in dichloromethane. Preliminary mechanistic investigations on the reversibility of the system allowed enhancing the selectivity (>20:1 dr, 73% ee). Relative configuration of the bicyclic compound was determined by X-ray crystal structure analyses.
Keywords: domino; organocatalysis; bicyclo[3.2.1]octane; β,γ-unsaturated 1,2-keto amide